Expression of peritumoral SPARC during distal cholangiocarcinoma progression and correlation with outcome. (2nd June 2020) - Byrling, Johannes; Sasor, Agata; Nilsson, Johan; Said Hilmersson, Katarzyna; Andersson, Roland; Andersson, Bodil
Abstract: Objectives: Distal cholangiocarcinoma (dCCA) is a malignancy with a dismal prognosis. One of the hallmarks is the presence of a rich desmoplastic stroma believed to contribute to tumor progression and treatment resistance. Secreted protein acidic and rich in cysteine (SPARC) is a matricellular glycoprotein implicated in tumor-stroma interaction with prognostic correlation across several malignancies. The aim of the present study was to evaluate the expression pattern and prognostic significance of SPARC in resected dCCA and paired lymph node metastasis. Materials and methods: SPARC expression was evaluated in 59 resected dCCA samples and 25 paired lymph node metastases as well as 10 benign bile duct samples using immunohistochemistry. Stromal SPARC expression was scored semi quantitatively. Survival was estimated using the Kaplan–Meier method with associated log-rank test. Results: SPARC expression was absent in normal bile ducts. In dCCA, peritumoral stromal SPARC was detectable in 47/59 (80%) of samples with 40/59 (68%) classified as high stromal SPARC expression. There was a significantly lower proportion of SPARC positive stroma in paired lymph node metastasis 17/25 (68%) than the corresponding primary tumors 24/25 (96%) ( p  = .016). Stromal SPARC expression was associated with the presence of lymph node metastasis; high SPARC expression 31/40 (78%) versus low SPARC expression 9/19 (47%) ( p  = .013). In the present material there was no significant association between stromal SPARC expression and survival. Conclusions: Stromal SPARC expression occurs frequently in dCCA. Although significantly lower than in primary tumors stromal SPARC is frequently retained in paired lymph node metastasis suggesting a possible role in the metastatic process of dCCA.